2019
DOI: 10.1016/j.semcdb.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of the renal vasculature

Abstract: The kidney vasculature has a unique and complex architecture that is central for the kidney to exert its multiple and essential physiological functions with the ultimate goal of maintaining homeostasis. An appropriate development and coordinated assembly of the different vascular cell types and their association with the corresponding nephrons is crucial for the generation of a functioning kidney. In this review we provide an overview of the renal vascular anatomy, histology, and current knowledge of the embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 175 publications
(233 reference statements)
1
34
0
Order By: Relevance
“…They concluded that LYVE-1 + cells initially bud off from veins but that LYVE-1 + macrophages and dendritic cells are crucial in orchestrating a branching process that connects these cells to extra-renal lymphatic vessels. VEGF-C also seems to have an essential regulatory role in this branching process ( Lee et al, 2011 ; Mohamed and Sequeira-Lopez, 2018 ). Tanabe et al (2012) similarly found that renal lymphatic vessels in the rat develop initially from pre-existing extrarenal lymphatic vessels and extend toward the cortex along the renal blood vasculature.…”
Section: Anatomy Of Renal Lymphaticsmentioning
confidence: 99%
“…They concluded that LYVE-1 + cells initially bud off from veins but that LYVE-1 + macrophages and dendritic cells are crucial in orchestrating a branching process that connects these cells to extra-renal lymphatic vessels. VEGF-C also seems to have an essential regulatory role in this branching process ( Lee et al, 2011 ; Mohamed and Sequeira-Lopez, 2018 ). Tanabe et al (2012) similarly found that renal lymphatic vessels in the rat develop initially from pre-existing extrarenal lymphatic vessels and extend toward the cortex along the renal blood vasculature.…”
Section: Anatomy Of Renal Lymphaticsmentioning
confidence: 99%
“…The issue of the development of the kidney vascularization is highly controversial [32]. Compelling evidence of sprouting angiogenesis has been provided [33].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is the formation of new blood vessels from the preexisting capillary network, which is a vital process in normal tissue development as well as the progression of several diseases, including inflammation, cancer, and diabetes (Musa et al, ; Mohamed and Sequeira‐Lopez, ). In the central nervous system, cerebral angiogenesis plays a role not only in the formation of brain vasculature during development but also in pathological events, such as the recovery of circulation after an ischemic stroke (Ruan et al, ).…”
mentioning
confidence: 99%